Cimicifuga racemosa Extract Ze 450 Re-Balances Energy Metabolism and Promotes Longevity - Malena Rabenau; Benjamin Dillberger; Madeline Günther; Sylvia Krippner; Veronika Butterweck; Georg Boonen; Jürgen Drewe; Gunter P. Eckert; Carsten Culmsee (Antioxidants, 2021)
Recently, we reported that the Cimicifuga racemosa extract Ze 450 mediated protection from oxidative cell damage through a metabolic shift from oxidative phosphorylation to glycolysis. Here, we investigated the molecular mechanisms underlying the effects of Ze 450 against ferroptosis in neuronal cells, with a particular focus on mitochondria. The effects of Ze 450 on respiratory complex activity and hallmarks of ferroptosis were studied in isolated mitochondria and in cultured neuronal cells, respectively. In addition, Caenorhabditis elegans served as a model organism to study mitochondrial damage and longevity in vivo. We found that Ze 450 directly inhibited complex I activity in mitochondria and enhanced the metabolic shift towards glycolysis via cMyc and HIF1α regulation. The protective effects against ferroptosis were mediated independently of estrogen receptor activation and were distinct from effects exerted by metformin. In vivo, Ze 450 protected C. elegans from the mitochondrial toxin paraquat and promoted longevity in a dose-dependent manner. In conclusion, Ze 450 mediated a metabolic shift to glycolysis via direct effects on mitochondria and altered cell signaling, thereby promoting sustained cellular resilience to oxidative stress in vitro and in vivo.